Respect for Life from the Point of View of Naturalness - Baďurová, Barbora (Studia Ecologiae et Bioethicae, 2022)
In daily debates, people often use the words “natural” and “naturalness”, and the meaning is often regarded as unproblematic. However, as the author points out, this can lead to misunderstanding in discussions, especially those regarding ethical matters. This paper relies mostly on philosophical methods of conceptual analysis and synthesis. The purpose of this study is to find answers to the question - Is respect for life natural and if so, in what sense? An analysis of several concepts of naturalness is presented, and later, applied to the concept of respect for life in environmental ethics for the purpose of synthesis. By analysing the concept of naturalness, the author is inspired, mostly by the investigations made by M. Sagoff and by H. Siipi. Regarding the findings, the author concludes that some senses of naturalness are not appropriate for the ethics of respect for life, because they are, for instance, not specific enough and ethically irrelevant in this context, while others may be useful in argumentation for respecting non-human living beings. The author claims that the most suitable sense seems to be the sense of naturalness in accordance with Aristotelian telos, although also modified for the sake of non-anthropocentric environmental ethics. Even though several authors dealt with the concept of respect for life and the concept of naturalness, this contribution enriches the discussion in the environmental ethics as it seeks answers to a question - if the respect for life is natural, in what sense of naturalness is it? The philosophical methods of asking related questions, and conceptual analysis of the term “naturalness”, as well as seeking its application and synthesis, can also be applied in schools when promoting the critical and philosophical thinking of students, who can, at once, become citizens dealing responsibly with ecological crisis and environmental problems.